The Legality And Legal Force of Girik As Collateral In Credit Provision By Rural Banks - Aditya Garingging, Jonatan (International Journal of Educational Research & Social Sciences, 2025)
This study aims to analyze the validity of using Girik documents as collateral in credit provision by Rural Credit Banks (BPR) based on the perspective of property security law and OJK regulations. Although Girik is administratively recognized in BPR practice based on POJK No. 1 of 2024, legally this document does not meet the requirements as an object of a security interest under Law No. 4 of 1996. Girik is merely proof of payment of land taxes and not proof of ownership rights over land, thus it cannot grant executory rights to creditors in the event of default. This study employs a normative legal approach that examines relevant laws and regulations and legal doctrines. The findings indicate the need for regulatory harmonization and strengthening of land rights conversion mechanisms to recognize documents like Girik as formal collateral. This study provides legal and policy recommendations for BPRs and regulators in establishing an inclusive credit system that ensures legal certainty and protection.